ANALISIS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH PT BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG PRABUMULIH - Mgs. M. Firdaus; Tien Yustini; Siti Komariah Hildayanti (Program Magister Manajemen Indo Global Mandiri University, 2021)
This study aims to obtain the results of the analysis of customer service on customer satisfaction at PT. Bank Negara Indonesia (Persero) Tbk Prabumulih Branch Offices partially and simultaneously. The research method uses quantitative and qualitative approaches, field data collection uses questionnaire and interview techniques. The population in this study amounted to 124 customers who transacted with customer service at BNI Prabumulih Branch Offices in August and September 2020 and the sample taken was 124 respondents. Testing data using the t test, the results showed that form / physical influence on customer satisfaction with t count 2.609> t table 1.980, reliability has no effect on customer satisfaction with t count 1.369 <t table 1.980, responses affect customer satisfaction with t count 2.298 > t table 1.980, assurance affects customer satisfaction with t count 9.907> t table 1.980, empathy has no effect on customer satisfaction with t count 0.443 <t table 1.980. The results of the F test show that form / physicality, reliability, response, assurance and empathy simultaneously influence customer satisfaction with F count 102.308> F table 2.292. The results showed that the service variable that had the most significant effect on customer satisfaction was the guarantee variable. Strategies to increase customer satisfaction can be done by maintaining indicators of polite attitudes towards customers, explaining products to customers, explaining customer data security and the ability to convince customers.